The Age-dependent Vertical Actions of Young Stars in the Galaxy - D. N. Garzon; Neige Frankel; Eleonora Zari; Maosheng Xiang; Hans-Walter Rix (The Astrophysical Journal, 2024)
Stars in the Galactic disk are born on cold, nearly circular orbits with small vertical excursions. After their birth, their orbits evolve, driven by small- or large-scale perturbations in the Galactic disk’s gravitational potential. Here, we study the vertical motions of young stars over their first few orbital periods, using a sample of OBA stars from Gaia E/DR3, which includes radial velocities and ages τ from LAMOST. We construct a parametric model for the time evolution of the stellar orbits’ mean vertical actions J _z as a function of Galactocentric radius, R _GC . Accounting for data uncertainties, we use Markov Chain Monte Carlo analysis in annuli of Galactocentric radius ( R _GC ) to constrain the model parameters. Our best-fit model shows a remarkably linear increase of vertical actions with age across all Galactocentric radii examined. Orbital heating by random scattering could offer a straightforward interpretation for this trend. However, various other dynamical aspects of the Galactic disk, such as stars being born in a warped disk, might offer alternative explanations that could be tested in the future.